Activities of Polish minority organisations in Central Asia on the example of the „Świetlica Polska” in Uzbekistan - Schmidt, Maciej (Mundus Slavicus I, 2025)
The purpose of the article is to present the main activities of the Polish minority organisations in the Central Asian countries on the example of the activity of the organisation from Uzbekistan, the „Świetlica Polska”. The author describes the ethno-politics of the countries in the region and characterises the Polish minority. The author describes in detail the activity of the largest Polish minority organisation in Uzbekistan, its educational and cultural activities and its cooperation with the Polish and Uzbek authorities.